2-Oxoadenosine induces cytotoxicity through intracellular accumulation of 2-oxo-ATP and depletion of ATP but not via the p38 MAPK pathway - Shinji Asada (Nature Portfolio, 2017)
Abstract 2-Oxoadenosine (2-oxo-Ado), an oxidized form of adenosine, is cytotoxic and induces growth arrest and cell death, which has potential as an anti-cancer drug. However, it is not well understood how 2-oxo-Ado exerts its cytotoxicity. We examined the effects of 2-oxo-Ado on non-tumour cells, namely immortalized mouse embryonic fibroblast lines, and investigated mechanisms by which 2-oxo-Ado exerts its cytotoxicity. We found that cell death induced by 2-oxo-Ado is classical caspase-dependent apoptosis, and requires its sequential intracellular phosphorylation catalysed by adenosine kinase (ADK) and adenylate kinase 2, resulting in intracellular accumulation of 2-oxo-ATP accompanied by accumulation of 2-oxo-Ado in RNA and depletion of ATP. Moreover, we showed that overexpression of MTH1, an oxidized purine nucleoside triphosphatase, prevents 2-oxo-Ado-induced cytotoxicity accompanied by suppression of accumulation of both intracellular 2-oxo-ATP and 2-oxo-Ado in RNA and recovery of ATP levels. We also found that 2-oxo-Ado activates the p38 MAPK pathway. However, siRNAs against Mkk3 and Mkk6, or treatment with several p38 MAPK inhibitors, except SB203580, did not prevent the cytotoxicity. SB203580 prevented intracellular phosphorylation of 2-oxo-Ado to 2-oxo-AMP, and an in vitro ADK assay revealed that SB203580 directly inhibits ADK activity, suggesting that some of the effects of SB203580 may depend on ADK inhibition.